iZZi Gadgets : sizing up the market opportunity - Shanahan, Doreen E.; Biseda, Marlene A. ([London] : SAGE, 2016)
As the CEO and one of the founders of iZZi Gadgets, Jayson Guzman had seen the entrepreneurial company grow from product inception in 2010 to product debut in 2013. The company's lens and case attachments enabled iPhone users' enhanced lens capability and improved photo-taking ergonomics. By the end of 2013, the firm had sold 2,500 units, and now, in April 2015, the firm generated revenues of nearly US$1.2 million. Jayson felt there was tremendous opportunity to grow sales for his company's products. He wanted to reach a broader audience with new products, to expand distribution, and to increase the company's investment in marketing. Expansion, however, would require additional funding. Jayson had secured an initial meeting with a potential investor to discuss the market opportunity. This case study examines this topic.
Description based on online resource; title from home page (viewed on May 3, 2016).
Keywords: elektronické knihy; electronic books; iZZi Gadgets (Firm); Marketing -- Management -- Case studies; New products -- Marketing -- Case studies; Small business marketing -- Case studies